Phonological loop and visuospatial sketchpad of working memory: comparison between Western and Chinese musical instrument background - Hue, Chi Yin; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Working memory has been positively associated with musical instrument background however lack of research has been considered types of musical instrument background are a factor that contributes to the findings. The research focused on studied the difference on phonological loop of working memory and visuospatial sketchpad of working memory between Western and Chinese musical instrument background among undergraduates. Besides, it also studied the relationship between phonological loop of working memory and visuospatial sketchpad of working memory among undergraduates with musical instrument background. Stratified random sampling was used to select a total 109 respondents from UPM, UKM and UM Western and Chinese music society. Among the samples, 54 and 55 undergraduate represent group of Western and Chinese musical instrument background. In this quantitative research, respondents were required to answer a short demographic questionnaire and computerized digit span and matrix span test which measured phonological loop of working memory and visuospatial sketchpad of working memory. The interesting finding of this research was there was a significant differences on phonological loop of working memory between the Western (M = 46.52, SD = 9.571) and Chinese musical instrument groups (M = 50.47, SD = 8.393; t (107) = -2.3, p = .02, two tailed) while Chinese musical instrument group have better score compare with Western musical instrument group. This indicated that type of musical instrument background is a factor that should take into consideration in the future research especially in phonological loop of working memory related study.